Implementasi Metode Pembelajaran Demonstrasi Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas VI Materi Tata Surya di MI NU Tamrinus Shibyan Pladen - Nuryana, Salma; Syifa, Layyinatus; Farah, Aliyya Ishlah; Hanik, Elya Umi (Lembaga Yasin AlSys, 2021)
This study aims to improve learning outcomes in class VI MI NU Tamrinush Shibyan Pladen by applying the demonstration method in science learning about the solar system material. The research is Classroom Action Research, which is carried out in one cycle through the stages of planning, implementation, observation and reflection. The subject of the study was a class VI MI NU Tamrinush Shibyan Pladen student. Data collection techniques consisted of interviews, observations, assessment rubrics, evaluation tests, and documentation. The test data were analyzed using the average grade and the percentage of student learning completeness. The results achieved in this study are in the first cycle the learning has been going well with the acquisition of an average grade of 83.3 with student learning completeness of 100%. Based on the results of the study, it was concluded that the application of the demonstration method to the science subjects of the solar system material could improve learning outcomes in class VI MI NU Tamrinush Shibyan Pladen.